Publicações sobre o método laboratório de mudança: seus objetos e intervenções - Ziotti, Giovane (2024)
The Change Laboratory (CL) is a formative intervention method that is theoretically and methodologically based on the Historical-Cultural Activity Theory (CHAT). The CL exists as a framework for interventions developed to transform work through the expansion of the objects of activity systems, thereby overcoming historical contradictions in the organization of work. This dissertation aims to understand how research that has applied or analyzed the Change Laboratory method in different contexts with various objectives has been published. To achieve this, a quantitative-qualitative research approach was developed through two systematic reviews, one bibliometric and the other qualitative. A total of 103 texts were selected and analyzed to produce a bibliometric analysis focusing on factors such as the number of texts published over the years, the origin of the publications, international participation in the research, authors, citations, journals or means of publication, and research institutions involved, types of texts, fields of knowledge of the research, and categories of professionals influenced by the interventions. Subsequently, using the same sample of texts, a qualitative systematic review was conducted, resulting in four different groups of publications based on their respective objects or purposes: when the object is unrelated to the CL; when the object is a CL intervention; when the object relates interventions to the development of theory; and when the object is the development of theory. For each of the groups, subcategories of publications were assigned based on the content of the analyzed texts. The discussions are made in light of CHAT, and the conclusions include a future research agenda that aligns with trends in the theoretical and methodological field of the CL.